2000
DOI: 10.1007/s002219900237
|View full text |Cite
|
Sign up to set email alerts
|

Instructing subjects to make a voluntary response reveals the presence of two components to the audio-vocal reflex

Abstract: Previous findings have shown that subjects respond to an alteration, or shift, of auditory feedback pitch with a change in voice fundamental frequency (F0). When pitch shifts exceeding 500 ms in duration were presented, subjects' averaged responses appeared to consist of both an early and a late component. The latency of the second response was long enough to be produced voluntarily. To test the hypothesis that there are two responses to pitch-shift stimuli and to clarify the role of intention, subjects were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
263
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 180 publications
(290 citation statements)
references
References 23 publications
23
263
4
Order By: Relevance
“…In an attempt to provide a quantitative hypothesis, we extended a previously presented model of F 0 control incorporating auditory feedback (Hain et al 2000), to include kinesthetic feedback. With our model we simulated our data and showed feasibility for a simple linear feedback implementation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In an attempt to provide a quantitative hypothesis, we extended a previously presented model of F 0 control incorporating auditory feedback (Hain et al 2000), to include kinesthetic feedback. With our model we simulated our data and showed feasibility for a simple linear feedback implementation.…”
Section: Resultsmentioning
confidence: 99%
“…We extended a linear model of F 0 control (Hain et al 2000) using auditory feedback to include kinesthetic input. This model topology is structured in a similar way to the speech production model of Guenther et al (2006), having both a feedforward and feedback pathway, and auditory and kinesthetic feedback.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A variety of studies have demonstrated that the introduction of changes to real time auditory feedback (to self-generated sounds during vocalization) elicits compensative reactions with a latency of 100-150 ms in listeners, with speech sounds (Xu et Hafke, 2008). It has been shown that compensative reactions to shifts in fundamental frequency remain the same when the listeners follow instructions not to respond to changes in feedback (Hain et al, 2000). In the aforementioned studies, various interval values were used to introduce changes in the voice fundamental frequency.…”
Section: Introductionmentioning
confidence: 99%